2011
DOI: 10.1590/s0034-71672011000500010
|View full text |Cite
|
Sign up to set email alerts
|

Óbitos associados à infecção hospitalar, ocorridos em um hospital geral de Sumaré-SP, Brasil

Abstract: This study investigated the socio-demographic profile, clinical procedures and etiology of nosocomial infection associated with deaths in the Hospital Estadual Sumaré, state of São Paulo, Brazil, from 2007 to 2008. The retrospective study of medical records (n = 133) revealed an average of 35 days of hospitalization. Most patients (97%) underwent some invasive procedure associated with nosocomial infection (p ≤ 0.05), including: 90 (67.7%) pneumonia, 62 (46.6%), urinary infections and 97 (73%) septicemia. Infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
14

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 15 publications
1
5
0
14
Order By: Relevance
“…A study performed in a hospital in São Paulo corroborates the results found in this study, which identified 15.4% of the deaths were associated with nosocomial infection and is considered the main cause of death in most studied patients [17].…”
Section: Resultssupporting
confidence: 88%
“…A study performed in a hospital in São Paulo corroborates the results found in this study, which identified 15.4% of the deaths were associated with nosocomial infection and is considered the main cause of death in most studied patients [17].…”
Section: Resultssupporting
confidence: 88%
“…Sendo assim, a execução de medidas de prevenção baseadas em evidências científicas é capaz de reduzir a incidência PAVM de forma significativa e sustentada, trazendo segurança na assistência e redução de custos, livrando o paciente de todas as implicações clínicas de uma infecção do trato respiratório hospitalar (GUIMARÃES et al, 2011).…”
Section: Pavm Pneumopatias Outrosunclassified
“…Além disso, a investigação precoce e precisa de multirresistência de microrganismos em ambiente hospitalar poderia ter impacto na redução da morbimortalidade. Neste sentido, a demora na liberação dos resultados de exames microbiológicos fere ao princípio da não maleficência, por proporcionar riscos importantes aos pacientes (17). No entanto, esta situação ainda envolve uma questão bioética em torno do princípio da justiça, considerando-se que esta morosidade pode estar relacionada à alta demanda, qualificação insuficiente e aparelhagem defasada nos laboratórios.…”
Section: Metodologiaunclassified